Liberação de nitrogênio em diferentes solos e épocas de cultivo sob adubação orgânica - Fioreze, Claudio (2010)
Organic fertilizers promote improvements in soil properties and are important in providing balanced nutrients to plants. The officials parameters adopted by the Commission of Chemistry and Soil Physics in the States of Rio Grande do Sul Santa Catarina to calculate the amount of organic fertilizer are its mean composition and the efficiency index of nutrient release (EINR) to fulfill the demand of each system crops. This indicator is related mainly to the type of organic residual, but the other factors affecting the mineralization are not adequately addressed, such as climatic conditions and soil texture, among others. The expectation of this work is that these factors are especially relevant in regions with large variation of soil types and climatic conditions, such as the South of Brazil region. So, the factors cropping season and soil texture were studied under the application of two different organic sources (pig slurry and chicken litter) in the field and in laboratory experiments. The texture effect was analyzed in an incubation of three soils containing 238, 470 and 605 mg clay kg soil-1, which was evaluated during 112 days of evolution of mineral nitrogen (N-NH4+ + N-NO3-), the net mineralization and % mineralization of total N and organic added. The influence of growing season was tested under field conditions in two crop series starting with the potato (summer and winter), which evaluated the productivity and nutrient cycling in three crops per system. The results of incubation showed that soil type affects the N dynamics in the soil after the addition of organic fertilizers. Most clayey soils make slowly immobilization and nitrification of ammonium, independently of addition of the broiler litter or pig slurry, which reduces the N pollution potential. The net N mineralization was greater in sandy soil due to lower physical-chemical protection of colloids. Also were greater with the chickens litter due to the amount of total N added have been much higher compared to pig slurry. The results of N available to plants (%NAP) and net mineralization of nitrogen in the soil (%Nminnet) with the addition of organic fertilizers indicate that EINR is overestimated in relation to N effectively added to the soils, and can result in depletion of soil organic matter in the long term growing. Also concludes that, to sandy soils or when manure are rich in available N, that must be done a N fractionated application between plantation and cover fertilization. In field experiments, there would significant differences in the efficiency of release of N in cropping systems of "summer" and "winter". The immediate effect was equal in the summer period to all fertilization sources, but in the winter the mineral source was 10-20% more efficient, showing the effect of temperature and soil moisture in the availability of N in soils under organic fertilization. The residual effect of chickens litter in the second crops was lower than expected in comparison to the pig slurry and mineral fertilizer, since the efficiency index of N liberation would be 20% for chickens litter and zero for the slurry. However only in the third crop that litter exceeded the slurry in dry matter production of summer crop (maize) and winter (black oat). Finally, due very different climatic conditions in South of Brazil, the results indicate that it necessary more and integrated studies about the impact of crop date and soil type to refine the parameters of the recommendation of organic fertilizer, making it thus more sustainable.